The challenge of the differential diagnosis between brown tumors and metastases in parathyroid carcinoma: a case report - Dinoi, Elisa; Prete, Alessandro; Sardella, Chiara; Pierotti, Laura; Della Valentina, Simone; Dal Lago, Anna; Borsari, Simona; Pardi, Elena; Caligo, Maria Adelaide; Michelucci, Angela; Torregrossa, Liborio; Rossi, Piercarlo; et al. (Frontiers in Endocrinology, 2024)
Background. Brown tumors are rare bone manifestations of primary hyperparathyroidism (PHPT) that may occur at different sites either as single or multiple lesions and they can easily be mistaken for malignant lesions. Neither bone site nor morphological or functional imaging are useful to drive the differential diagnosis and biopsy is often the only conclusive procedure.Case description. We report the case of a 53 years-old man referred to our outpatient clinic for severe symptomatic PHPT complicated by nephrolithiasis and osteoporosis. Neck ultrasound and computed tomography (CT) scan showed a large irregular lesion posterior to the lower pole of the right thyroid lobe consistent with an enlarged parathyroid gland. Moreover, two bone lytic lesions were described at the left scapula and the contiguous 7 th rib that showed an increased uptake at total bone scintigraphy. Given the clinical and biochemical picture, the features of the parathyroid lesion and the presence of bone lytic lesions, the suspicion of metastatic parathyroid carcinoma (PC) was raised. However, a CT-guided biopsy performed on the left scapula revealed a brown tumor. The patient underwent en-bloc resection of the right inferior parathyroid grand with the ipsilateral thyroid gland lobe. Histopathology confirmed the diagnosis of PC. Postsurgical biochemical evaluations showed that the patient was cured. A repeated total body CT scan revealed an osteoblastic appearance of the bone lesions ascribed to the partial regression of the brown tumors following surgery.Conclusions. The implication of a diagnosis of brown tumor or bone metastasis is widely different; in fact, the first tends to regress with the surgical treatment of PHPT, whereas the latter has limited cure option and negatively affects the prognosis of patients. Therefore, although brown tumors are extremely rarer than in the past, they must always be taken into consideration in the presence of bone lesions, even in cases of high suspicion of malignancy, to avoid unnecessary and harmful surgical interventions.